European Portuguese version of the Child Self-Efficacy Scale: A contribution to cultural adaptation, validity and reliability testing in adolescents with chronic musculoskeletal pain. (October 2020) - Andias, Rosa; Silva, Anabela G.
Abstract: Background: Pain Self-efficacy is an important resilience mechanism in adolescents with chronic musculoskeletal pain. The Child Self-Efficacy Scale (CSES) was developed to assess self-efficacy related to functioning despite pain. Objectives: This study aimed to cross-culturally adapt the CSES into European Portuguese and to assess its validity and reliability in a sample of adolescents with chronic musculoskeletal pain. Methods: The original version of the CSES was translated and pilot tested in line with international guideless. Then, the European Portuguese version was filled in by 1730 adolescents, who also completed the following instruments: Nordic Musculoskeletal Questionnaire; Numeric Pain Rating Scale; Pain Catastrophizing Scale; Depression, Anxiety and Stress Scale; Tampa Scale of Kinesiophobia, and Basic Scale on Insomnia Complaints and Quality of Sleep. Sixty-three of these adolescents, with at least one painful body site, completed the questionnaire twice to assess test-retest reliability and measurement error. Internal consistency was obtained, and hypothesis testing and factor analysis were used to assess validity. Results: Cronbach's alpha ranged from 0.89 to 0.92, ICC was 0.83 (95%CI: 0.71; 0.89), the SEM and MDD were 2.49 and 6.9, respectively. Fair and moderate to good correlations were found between CSES and catastrophizing (rs from 0.45 to 0.48), depression, anxiety and stress (rs from 0.35 to 0.38), fear of movement (rs from 0.38 to 0.49) and sleep (rs from 0.20 to 0.29). The factor analysis resulted in 1-factor model. Conclusion: The European Portuguese version of the CSES appears to be valid and reliable in adolescents with chronic musculoskeletal pain. Highlights: The European Portuguese version of the CSES was considered easy to understand by adolescents with chronic pain. The European Portuguese version of the CSES appears to be valid in adolescents with chronic pain. The European Portuguese version of the CSES appears to be reliable in adolescents with chronic pain.